A Study on Environmental Issues In India: Exploring Strategies and Challenges in Addressing Environmental Issues (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The environmental movement has achieved a great deal inattempting to meet environmental issues, investing remarkable effort withlimited funding against powerful countervailing forces. In these attempts, theenvironmental movement pursues two basic types of strategy: engagingorganizations (both government and businesses) and engaging the particularbehaviours that individual citizens pursue. In the current study , an overviewof these two strategies as a prelude to introduce a third approach to which theenvironmental movement must pay close attention. This third approach holdssubstantial promise for enhancing the effectiveness of the movement’s currentwork and for developing useful strategies for new types of intervention. The natural world can be a dramatic, dynamic anddangerous place. Life ultimately thrives on Earth because it is a dynamicplanet, but the extremes of nature can threaten the survival of individuals,communities and even species. Every year television pictures and newspapersreport scenes of devastation, despair and death caused by huge earthquakes,floods, droughts, cyclones, landslides and volcanic eruptions. The Asiantsunami, with around 250 000 deaths, huge economic losses and long term damageto development programmes in the affected countries, brought home to the worldthe realities of the danger.